OPTIMIZATION OF FDM 3D PRINTING PARAMETERS ON THE TENSILE STRENGTH OF FOOD-GRADE PLA FILAMENT USING THE TAGUCHI METHOD - Pristiansyah, Pristiansyah; Hasdiansah, Hasdiansah; Subhan, Muhammad; Sukanto , Sukanto; Aswin , Fajar; Masdani , Masdani; Ariansyah , Ariansyah (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Additive manufacturing, particularly 3D printing, has emerged as a transformative technology in digital fabrication, enabling the rapid, accurate, and cost-effective production of complex components. Among the various 3D printing methods, Fused Deposition Modeling (FDM) is one of the most prevalent techniques, employing thermoplastic filaments as its primary material source. This research aims to determine the optimal process parameters to achieve the highest tensile strength in components fabricated using food-grade Polylactic Acid (PLA) filament. To accomplish this, the Taguchi method was implemented as a robust design tool to optimize the manufacturing process, improve material performance, and reduce both cost and resource consumption. The experimental design followed the L27 Orthogonal Array, and the analysis was conducted using the Signal-to-Noise Ratio (SNR) to identify the most significant parameter combinations affecting tensile strength outcomes. The investigated process parameters included extruder temperature, build plate temperature, layer thickness, infill pattern, and deposition speed. Based on the results, the optimal conditions for maximizing tensile strength were identified as follows: extruder temperature of 190 °C, build plate temperature of 60 °C, layer thickness of 0.2 mm, triangle infill pattern, and deposition speed of 60 mm/s. Additionally, the parameters with the greatest influence on tensile strength, ranked from most to least impactful, were: build plate temperature, layer thickness, infill pattern, deposition speed, and extruder temperature.